PENDIDIKAN ISLAM MELAYU DAN MODERASI BERAGAMA - Lailatul Mukjizat; Saipul Annur; Choirun Niswah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study examines the strategic role of Malay Islamic education in shaping the moderate character of Muslims in a pluralistic and multicultural society. Malay Islamic education is a system that integrates Islamic teachings with Malay cultural values such as tawasuth (balance), tawazun (harmony), i'tidal (justice), tasamuh (tolerance), musawah (equality), and shura (deliberation). Through a holistic approach encompassing cognitive, affective, and psychomotor aspects, these values of moderation are instilled in educational environments such as madrasahs (Islamic schools), Islamic boarding schools (pesantren), and families. This study uses a descriptive qualitative method with a literature review approach to examine the contribution of Malay Islamic education in internalizing the values of religious moderation. The results indicate that Malay Islamic education serves not only as a means of transmitting knowledge but also as a bulwark against radicalism and intolerance, as well as a key pillar in building a harmonious, just, and civilized society.